Analysis of the Effect of Transformational Leadership on University Performance with Learning Organization and University Culture as Intervening Variables (Case Study International Women University) - Evi Sofiati; Jajang Permana; Triyani Triyani; Andreas Wahyu Gunawan P; Stefanus M S Sadana (Budapest International Research and Critics University, 2022)
This study aims to test and analyze the influence of transformational leadership on university performance with learning organization and university culture as intervening variables. Samples and data in this study were obtained from 73 international Women University students using questionnaires. Sample selection was carried out by purposive sampling. The hypothesis in this study was tested using the Partial Least Square (PLS) method and descriptive analysis using SPSS. The results showed that transformational leadership had a positive and significant effect on university performance with an influence on the structural level relatively close to moderate. Transformational leadership has a significant and positive effect on learning organizations and university culture. Learning organizations and university culture have a positive effect on university performance. Learning organizations in mediating the indirect influence of transformational leadership on university performance have no significant influence. University culture in mediating the indirect influence of transformational leadership on university performance has a significant influence.